Cryptic variation in RNA-directed DNA-methylation controls lateral root development when auxin signalling is perturbed - Shahzad, Zaigham; Eaglesfield, Ross; Carr, Craig; Amtmann, Anna (Nature communications, 2020)
Maintaining the right balance between plasticity and robustness in biological systems is important to allow adaptation while maintaining essential functions. Developmental plasticity of plant root systems has been the subject of intensive research, but the mechanisms underpinning robustness remain unclear. Here, we show that potassium deficiency inhibits lateral root organogenesis by delaying early stages in the formation of lateral root primordia. However, the severity of the symptoms arising from this perturbation varies within a natural population of Arabidopsis and is associated with the genetic variation in CLSY1 , a key component of the RNA-directed DNA-methylation machinery. Mechanistically, CLSY1 mediates the transcriptional repression of a negative regulator of root branching, IAA27 , and promotes lateral root development when the auxin-dependent proteolysis pathway fails. Our study identifies DNA-methylation-mediated transcriptional repression as a backup system for post-translational protein degradation which ensures robust development and performance of plants in a challenging environment. Developmental plasticity of plant root systems has been intensively studied, but the mechanisms underpinning robustness remain unclear. Here, the authors show that DNA-methylation-mediated transcriptional repression serves as a backup system to control lateral root development when auxin signalling is perturbed.